“Stranger Things”: the future of Latin American regionalism - María Victoria Alvarez (Revista Conjuntura Austral, 2020)
Latin American attempts at regionalism have been pursued through different waves. The last wave, post-liberal or post-hegemonic regionalism, is fading. Building on contributions from International Political Economy, European Studies and International Relations, the paper aims at answering two main questions: how can we characterize the current paths of regional integration in Latin America considering the trends of the last ten years? What can we expect of Latin American regionalism over the next decade? Grounded on a qualitative content analysis, we address three premises based on the past trajectory of Latin American regionalism in order to grasp some of the present and (possible) futures trends: membership of regional organizations, institutional design of regional organizations and the role of the United States. After contrasting these elements with recent Latin American regionalist developments, the paper engages in a creative exercise of forecasting. The purpose is not to pretend to know the future nor to predict it but to present two imaginable scenarios: a short-term scenario and a longer-term scenario. Maybe we are about to witness some “stranger things” in the future of Latin American regionalism, opening up to different realities, different explanations and alternatives.